Industrial strength bluegrass : Southwestern Ohio's musical legacy - Bartenstein, Fred, 1950-; Ellison, Curtis W. (Music in American life., 2021)
"In the twentieth century, Appalachian migrants seeking economic opportunities relocated to southwestern Ohio, bringing their music with them. Between 1947 and 1989, they created an internationally renowned capital for the thriving bluegrass music genre, centered on the industrial region of Cincinnati, Dayton, Hamilton, Middletown, and Springfield. Fred Bartenstein and Curtis W. Ellison edit a collection of eyewitness narratives and in-depth analyses that explore southwestern Ohio's bluegrass musicians, radio broadcasters, recording studios, record labels, and performance venues, along with the music's contributions to religious activities, community development, and public education. As the bluegrass scene grew, southwestern Ohio's distinctive sounds reached new fans and influenced those everywhere who continue to play, produce, and love roots music. Revelatory and multifaceted, Industrial Strength Bluegrass shares the inspiring story of a bluegrass hotbed and the people who created it"--